Effect of information encounter on concerns over healthy eating- mediated through body comparison and moderated by body mass index or body satisfaction - Piper Liping Liu; Angela Chang; Matthew Tingchi Liu; Jizhou Francis Ye; Wen Jiao; Harris Song Ao; Weixing Hu; Kaibin Xu; Xinshu Zhao (BMC, 2023)
Abstract Background Understanding factors that influence healthy or unhealthy eating can inform intervention strategies. This study ascertained whether and how unintentional exposure to food and nutrition information influenced healthy eating concerns. The study tested body comparison, body satisfaction, and body mass index as three mechanisms that potentially link food information encounter, commonly known as information scanning, to healthy eating concerns. Methods A sample of 440 online participants (mean age = 29.15 years) was used to investigate: (1) how unintentional exposure to food and nutrition information, i.e., information encounter (IE), affects healthy eating concerns (HEC); (2) how the effect of IE on HEC is mediated by body comparison (BC); (3) how the paths of the mediation model are moderated by body satisfaction (BS) or body mass index (BMI). Results The findings show a positive and sizable total effect of IE on HEC - a whole-scale increase in information encounter is associated with a substantial increase in healthy eating concerns by 15 percentage points (b p  = 0.150). BC is found to mediate the effect of IE on HEC in an all-positive complementary mediation. Both the indirect and the direct-and-remainder paths show sizable effects. The mediated path contributes about 20% of the total effect between IE and HEC (c p  = 20%), while the direct-and-remainder path contributes the rest (c p  = 80%). BS was found to moderate the relationship between IE and BC, the first leg of the mediation. The moderation effect is large - the effect of IE on BC is much smaller on the highly and the moderately satisfied than on the lowly satisfied (slope differential b p  = -.60). BMI was found to moderate the direct-and-remainder effect of IE on HEC, controlling BC. That is, the effect of IE on HEC, after filtering out the mediated effect through BC, is much larger for those with high or low BMI than those with healthy BMI (slope differential b p  = .32). Conclusions Exposure, even if unintentional, to food and nutrition information is an important predictor of HEC. BC, BS, and BMI are important factors that help to explain the process through which information affects behaviors.